Comparative strength of I section pavement blocks made of PCC mixed with rice husk ash - Debnath, Sohang; Durga Naga Laxmi, D (International Journal of Engineering and Technology, 2018)
Originally, pavement solid blocks mold by raw products of brick like clay, fly ash or lime etc. from decades, the solid blocks are commonly casted for getting the keen ambiance for footpath ways. The dismantled solid blocks are reusable in a cost effective way without any pre existing mark.Now-a-days updated technology is giving us a chance to enhance methods in various aspects related to execution of field works like pavements etc.This study determine the comparative strength of I section pavement blocks are casted in 2 ways. They are i) 100% pure PCC which contains cement, fines (FA) and coarse (CA) and ii)PCC mix proportion which is shared a part % of organic additive like rice husk ash added to identify the variation of characteristic strength.The organic supplement is added with PCC in terms of % proportions like 5%, 10% and 15%, to find out the properties of strength for 3,7,14 and 28 days of casted curing blocks. Based on study we noticed that compacting factor test reduces the % with organic additive RHA which improves the strength in a cost effective manner.This paper indicates the organic additive plays a key role to attain high strength of concrete and it indicates clearly the downfall towards self weight to measure the strength with respect to pure PCC.Â Â